Meta Analysis: The Role of Herbal Medicines in the Management of Functional Gastric Disorders - Nur Cahyani Tahir; Syamsu Rijal; Sabruddin Sabruddin (Newinera Publisher, 2026)
Functional gastric disorders (FGDs), including functional dyspepsia, are highly prevalent worldwide and significantly affect patients’ quality of life. Herbal medicines are increasingly used as complementary therapies, yet their overall effectiveness remains uncertain due to variability across studies. This study aimed to evaluate the effectiveness of herbal medicines in the management of functional gastric disorders through a systematic review and meta-analysis. A systematic literature search was conducted in PubMed, Scopus, Web of Science, ScienceDirect, and relevant national databases for studies published between 2015 and 2025. The review followed PRISMA guidelines. Randomized controlled trials assessing herbal interventions in adults with FGDs were included. Data were analyzed using a random-effects model due to substantial heterogeneity. Effect sizes, 95% confidence intervals (CI), and heterogeneity indices (Q, I², τ²) were calculated. Five randomized controlled trials met the inclusion criteria. The pooled effect size was 0.105 (95% CI: 0.000–0.216; p ≈ 0.050), indicating a small but positive effect of herbal medicines on symptom improvement. However, heterogeneity was very high (I² = 98.90%), reflecting considerable inter-study variability. Herbal medicines demonstrate modest potential as complementary therapies for FGDs. Nevertheless, the small effect size and high heterogeneity warrant cautious interpretation and highlight the need for larger, high-quality clinical trials.